TiO2 sol-gel coating as a transducer substrate for impedimetric immunosensors - Dorledo de Faria, Ricardo Adriano (Array, 2020)
Given the importance of the transducer elements in the performance of sensors for various applications, as well as the growing search for devices that are capable of providing the response in shorter time, in this work, titanium dioxide was examined as a candidate for application in an electrochemical biosensor. A TiO2 coating deposited by sol-gel method on a silicon wafer was obtained with an anatase crystalline structure, as an n-type semiconductor with donor density equal to 2.954 · 1017 cm–3. Its surface was functionalized to be tested as a biosensor to detect snake venom of the Bothrops genera, and each step of the functionalization was investigated using Electrochemical Impedance Spectroscopy (EIS) and Cyclic voltammetry. Despite being less sensitive than the reference method ELISA, the TiO2-based biosensor was also capable of detecting the analyte of interest at 20 μg mL–1, revealing an increase in its leakage resistance and phase shift after incubation in this solution. Furthermore, the total time for carrying out the biodetection with the TiO2-coated device (41.24 ± 0.05 min) was estimated to be approximately 80 % shorter than that required by the labelled standard assay, which indicates that TiO2 is a promising electrochemical transducer for biosensing applications.